Estimation of Peoples’ Perception on Climate Change Effect on Agriculture: A Participatory and Socio-personal Analysis - A Jena; S K Acharya (Indian Journal of Extension Education, 2016)
Climate change has been recognized globally as an ever increasing threat. The economic and social implications of global climate change are the subject of intense national and international study in present day scenario. The present study has delved deeper into the peoples’ perception on congenital effect of climate change on agriculture in regards to coastal agroecosystem of Odisha. The study has been based on a blend between participatory rural appraisal and a conventional multivariate statistical analysis including correlation coefficient, multiple regression analysis, path analysis, factor and canonical covariate analysis. Almost every year, within a cohort of last 53 years, coastal agriculture of Odisha has experienced brunt of 40 years of drought, flood or cyclones. This has been reflected in the stagnating yield of food crops over the couple of decades, negating the positive impact of modern technology and fertilizer application in the operating farms. The result shows that, the variables like, age (X1), education (X2) & changing expenditure allocation on education (X10), change pattern of watching television, listening to radio, all have been redeemed into a dependable estimator of perception on climate change effect on agriculture.